A surprisingly simple electrostatic model explains bent vs. linear structures in M+-RG2 species (M = group 1 metal, Li–Fr; RG = rare gas, He–Rn) - Andrejeva, Anna; Breckenridge, William; Wright, Timothy G. (American Chemical Society, 2015)
It is found that a simple electrostatic model involving competition between the attractive dispersive interaction and induced-dipole repulsion between the two RG atoms performs extremely well in rationalizing the M+-RG2 geometries, where M = Group 1 metal and RG = rare gas. The Li+-RG2 and Na+-RG2 complexes have previously been found to exhibit quasilinear or linear minimum energy geometries, with the Na+-RG2 complexes having an additional bent local minimum [A. Andrejeva, A. M. Gardner, J. B. Graneek, R. J. Plowright, W. H. Breckenridge and T. G. Wright, J. Phys. Chem. A, 2013, 117, 13578]. In the present work, the geometries for M = K–Fr are found to be bent. A simple electrostatic model explains these conclusions and is able to account almost quantitatively for the binding energy of the second RG atom, as well as the form of the angular potential, for all thirty six titular species. Additionally, results of population analyses are presented together with orbital contour plots; combined with the success of the electrostatic model, the expectation that these complexes are all physically bound is confirmed.